RELATIONSHIP BETWEEN OIL CONTENT IN SEDIMENT AND MACROZOOBENTOS ABUNDANCE IN SELAT BARUCOASTAL WATERS OF BENGKALIS REGENCY RIAU PROVINCE - Mahzwan Putra Pratama; Bintal Amin; Elizal Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in September 2017to determine the oil content in sediments, the abundance of macrozoobentos in sediments and their possible relationship in the coastal waters of Selat Baru Bengkalis, Riau. Three sampling stations with three replications in each station were surveyed. Sediment samples were taken and placed in labelled plastics bags and transported to laboratory for later analysis at the Faculty of Fisheries and Marine Science. The macrozoobentos samplewas given a few drops of 10% formalin solution and then taken to the laboratory for later identification. The oil content of sediment in Selat Baru coastal waters ranges from 917.87 to 5595.73 ppm, with the highest oil content being found at station 1 (around the harbour) and the lowest was at Station 2 (coastal tourism area). The types of macrozoobentos found in Selat Baru coastal waters consist of two classes namely, gastropods and crustaceans. Species of macrozoobenthos which have relatively high abundance value at each sampling point isCerithidea sp. Based on simple linear regression, the relationship between the oil content in sediment with the abundance of macrozoobentos was categorized as a moderate relationship (y = 16.03-0.001x; R2 = 0.588,r = 0.76) which indicated that the higher the oil content, the lower the macrozoobenthos abundance in sediment.Keywords: Pollution, Oil, Sediment, Makrozoobentos